2015
DOI: 10.1371/journal.pone.0143437
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Features of Skeletal Metastases: A Comparative Study between Pulmonary and Prostate Cancers

Abstract: Bone scintigraphies are widely applied for detecting bone metastases. The aim of this study was to investigate distribution features of bone metastases in pulmonary and prostate cancers. Bone scintigraphies were performed in 460 patients with pulmonary cancer and 144 patients with prostate cancer. Patients were divided into three groups according to the total number of bone metastases: few bone metastases, moderate bone metastases, and extensive bone metastases. We compared the distribution of bone metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Especially among patients with only one bone containing a metastasis but no visceral metastases, we observed the characteristics of bone metastatic distribution that neighboring bones to the primary were more likely to be first metastasized. This also correspond to previous findings that the differences in the distribution of bone metastases between pulmonary, breast and prostate cancers [7], [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Especially among patients with only one bone containing a metastasis but no visceral metastases, we observed the characteristics of bone metastatic distribution that neighboring bones to the primary were more likely to be first metastasized. This also correspond to previous findings that the differences in the distribution of bone metastases between pulmonary, breast and prostate cancers [7], [11].…”
Section: Discussionsupporting
confidence: 92%
“…Metastases carried through the circulatory system may spread to any bone in the body, as this pathway is considered to be random [7]. Although numerous studies have been published about systemic circulatory bone metastases, few studies had addressed bone metastasis through the vertebral venous plexus [8], [9], [10], [11], and the pattern of vertebral venous plexus related bone metastasis had not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…While, previous researchers found that the ribs then the spinal region were the most common sites 3,8 which can be attributed to direct tumor invasion.…”
Section: Discussionmentioning
confidence: 92%
“…The bony pelvis is a favored site for PCa bone metastases (14, 15). Additionally, patients who develop pelvic bone metastases may have worse OS (16).…”
Section: Introductionmentioning
confidence: 99%